What to do about the (dis)protection of children and adolescents? A topic debated in the Degree in History (Clío & Asociados. La historia enseñada. ISSN: 2362-3063, 2023)
This article seeks to present a theoretical-practical reflection on the experience of future history teachers, graduates of the Federal Rural University of Pernambuco (UFRPE), and operators of the rights of children and adolescents (guardianship counselors) in Brazil. A dialogue that allowed the development of an epistemological reflection on education and social issues, especially the relationship between teaching, school and the network for the protection of children and adolescents. In the first part, we will present the scenario of practice and reflection and the idea of a safety net. In a second moment, we presented a debate on how these agents became the main articulators between the school, the community and the child protection network. Next, we will treat the school as a space of protection and the role that the history teacher can play to face violence and defend the rights of children and adolescents. Finally, we point out some knowledge and actions necessary for the teacher to face the social challenges of the present and the future in the Brazilian school space, showing how the dialogue of this fruitful pedagogical encounter took place.
Keywords: teacher education; rights; protection